Relationship between Remittance and Economic Growth in Nepal - Kaphle, Raghu Raj (Tribhuvan University Journal, 2019)
For the period between 1976 and 2017, this study investigates the relation from remittances and trade to economic growth. Study applied time series econometric techniques; unit root, cointegration and error correction mechanism to examine long-run and short-run association between dependent and independent variables. Outcome confirms a long-run relationship between remittance, trade and economic growth. However, no short-run causal relationship exists between remittances and economic growth, but trade showed significant influence even in the short run in GDP for the period of analysis. The paper also discusses about the effective utilization of remittances. It is hoped that the study would be helpful to government and policy makers for domestic policy formation in the area of utilization of remittances and management of migration from Nepal.